Development of blueberry liquor: influence of distillate, sweetener and fruit quantity. (1st September 2017) - Caldeira, Ilda; Lopes, Daniel; Delgado, Teresa; Canas, Sara; Anjos, Ofélia
Abstract: BACKGROUND: In this work different formulations of blueberry liquor were tested and characterised based on their physico‐chemical and sensory characteristics. RESULTS: Three factors were evaluated: the distillate used to produce the liquor (wine spirit or grape marc spirit); the sweetener (white sugar or honey) and the fruit quantity (two doses). For each liquor, pH, total acidity, dry soluble solids content, dry extract, alcoholic strength, reducing sugars, colour intensity, methanol content, acetaldehyde and fusel alcohols were determined. Sensory tests were carried out with a trained panel. CONCLUSION: The three factors studied significantly influenced the physico‐chemical features of the liquors, being the quantity of fruit the most discriminating factor, except for the volatile compounds which were mainly influenced by the distillate. As regards the sensory analysis, it was found that the most appreciated liquor was that prepared with wine spirit, sugar and a lower dose of blueberry, and the less appreciated formulation was the one made with grape marc spirit, honey and a lower quantity of blueberry. © 2017 Society of Chemical Industry